College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 1, Equations and Graphs - Section 1.4 - Solving Quadratic Equations - 1.4 Exercises: 38

Answer

$-\frac{3\pm\sqrt{13}}{4}$

Work Step by Step

First we multiply through by 2: $2x^{2}+3x-\frac{1}{2}=0$ Then we solve using the quadratic formula: $4x^{2}+6x-1=0$ $x=\frac{-b\pm\sqrt{b^{2}-4ac}}{2a}=\frac{-6\pm\sqrt{6^{2}-4(4)(-1)}}{2(4)}=\frac{-6\pm\sqrt{52}}{8}=-\frac{3\pm\sqrt{13}}{4}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.